Retrospective statistical analysis on the diagnostic value of ductography based on lesion pathology in patients presenting with nipple discharge. Issue 4 (13th May 2019) - Srinivasan, Ashmitha; Nia, Emily; Gupta, Monali; Sun, Jia; Leung, Jessica WT
Abstract: Purpose: To compare sensitivities and specificities of ductography to noninvasive imaging studies in determining the cause of nipple discharge and assess the value of ductography on the basis of pathologic results. Methods: In this retrospective review of women with nipple discharge who underwent ductography between January 1, 2005 and October 30, 2015, at our institution, we compared ductography with noninvasive imaging results (mammography, ultrasound, MRI) to determine its relative diagnostic sensitivity, specificity, and relative accuracy. Diagnosis was defined from pathology results, clinical notes, and minimum of 1‐year follow‐up monitoring. The primary endpoints include accuracy, sensitivity, specificity, positive predictive value, and negative predictive value. The analyses were carried out in different configurations to compare results by the following pathologic categories: cancer, high‐risk lesion, intraductal papilloma (IP) without atypia, and benign pathology and/or normal imaging results. Results: In patients with breast cancer, ductography and noninvasive breast imaging had similar sensitivities. In patients with a high‐risk lesion, ductography was significantly more sensitive than noninvasive imaging modalities. In patients with intraductal papilloma without atypia, ductography was more sensitive than noninvasive imaging, but the difference was of only borderline significance. For women with benign pathology and/or normal imaging, noninvasive imaging showed a significantly higher specificity than ductography. Conclusion: In the absence of standard diagnostic algorithm for patients presenting with nipple discharge, the clinician has numerous options to choose a diagnostic approach that will yield the most accurate information with the least disruption to the patient. Our results indicate the value of ductography compared to value of noninvasive imaging modalities when cancer is suspected and when high risk lesion is suspected. While we show the sensitivity of ductography is similar to noninvasive imaging modalities in the setting of cancer, the sensitivity of ductography is statistically valuable for diagnosing high‐risk lesions. Our hope is that this study will emphasize more research and more understanding in clinical utility and management of high‐risk lesions, leading to patient‐focused algorithm for diagnosing the etiology of abnormal nipple discharge.